Developing Causal Loop Diagram for Urban Development and Land Carrying Capacity in Surakarta - Arsianti, Ari; Astuti, Winny; Suryanto, Suryanto; Candraningtyas, Callista Fabiola; Primabudi, Eko (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Surakarta has an area of 46.72 km2 with a population of 583,961 people. The land use in Surakarta for housing is 62% and for open space is only 9.82% of the area. Meanwhile, economic growth in this city has always experienced an increasing trend, where in 2023 investment growth reached 55.82%. This study aims to determine the general picture through the causal relationship between the components of urban development and the carrying capacity of land in Surakarta. This study uses a quantitative descriptive approach. Data is obtained from identified variables which are then arranged dynamically using Causal Loop Diagram (CLD) analysis processed with Vensim software. The results show that there is a supply model (built-up area and green open space) and a demand model (population, investment, and Gross Domestic Product). The relationship between variables describes the causal relationship in Surakarta's Land Carrying Capacity divided into three rounds, namely Loop B1 (Land Carrying Capacity – Demand - Supply - Land Carrying Capacity), Loop B2 (Supply - Built-up Land - Land Conversion - Green Open Space – Supply), and Loop R1 (Population - Demand - Investment - GDP - GDP per capita – Population).